2018
DOI: 10.1088/1674-1056/27/8/084209
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and modulation of terahertz radiation by multi-color laser pulses

Abstract: We study theoretically intense terahertz radiation from multi-color laser pulse with uncommon frequency ratios. Comparing the two-color laser scheme, of which the uncommon frequency ratio should be set to be a specific value, we show that by using multi-color harmonic laser pulses as the first pump component, the lasers as the second pump component can be adjusted in a continuous frequency range. Moreover, these multi-color laser pulses can effectively modulate and enhance the terahertz radiation, and the tera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Numerically we have investigated the properties of the combination components 3ω ± 2∆ω, the results are shown on Figure 3 (the spectral density near the third harmonic for pulses with two different values of ∆ω) and Figure 4 (the dependence of intensities of 3ω ± 2∆ω on the intensity of one of the components with fixed intensities of two other in a three-color pulse and ∆ω = 0.07ω). Expression (15) does not correctly describe the entire form of the dependence of dj 3ω+2∆ω /dt on µ 1,2 , since to do this, it is necessary to take into account all the significant higher orders of the IMWM. However, already from it one can see some properties of the generation of a given combination frequency, such as linearity in both amplitudes at low values, and a slight asymmetry: if we put µ 1 = µ 2 and change the sign of ∆ω, we see that when the intensities of both additional components are equal, the low-frequency satellite of the third harmonic should have a slightly larger amplitude, which is confirmed by both semiclassical and quantum mechanical calculations.…”
Section: Numerical Calculations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerically we have investigated the properties of the combination components 3ω ± 2∆ω, the results are shown on Figure 3 (the spectral density near the third harmonic for pulses with two different values of ∆ω) and Figure 4 (the dependence of intensities of 3ω ± 2∆ω on the intensity of one of the components with fixed intensities of two other in a three-color pulse and ∆ω = 0.07ω). Expression (15) does not correctly describe the entire form of the dependence of dj 3ω+2∆ω /dt on µ 1,2 , since to do this, it is necessary to take into account all the significant higher orders of the IMWM. However, already from it one can see some properties of the generation of a given combination frequency, such as linearity in both amplitudes at low values, and a slight asymmetry: if we put µ 1 = µ 2 and change the sign of ∆ω, we see that when the intensities of both additional components are equal, the low-frequency satellite of the third harmonic should have a slightly larger amplitude, which is confirmed by both semiclassical and quantum mechanical calculations.…”
Section: Numerical Calculations and Discussionmentioning
confidence: 99%
“…This can be done using the frequency tuning of the ionizing pulse components in optical parametric generators [11][12][13]. Recently, the possibility of using multi-color (three or more) pulses instead of traditional two-color ionizing pulses has been increasingly investigated [13][14][15][16]. The solution of optimization problems for such systems is complicated by the fact that the extremely nonlinear nature of ionization-induced multiwave mixing (IMWM) manifests itself in a strong interdependence of the optimal values of each pulse parameter on the values of all others [14,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Air plasma has always been a major topic in the field of THz sources due to its nondamage threshold. [14][15][16] Hamster et al found that THz radiation can be observed from plasma generated by ambient air and excited with an ultrafast pulse laser. [17,18] With further research, several approaches have been proposed to modulate air plasma and thereby enhance THz radiation.…”
Section: Introductionmentioning
confidence: 99%